Poder discrecional de la corte constitucional en el estado de cosas inconstitucional (2012)
This paper is an academic reflection that aims to show how in individual casesunder the discretionary power of constitutional judges, explains the uniqueness ofthe processes of constitutional interpretation fromvalues and principles in thepursuit of protection of fundamental rights and dueto the constitutionalization ofthe law may validly act outside the scope of its competence, under the protection ofwhat the Constitutional Court has called “ The Unconstitutional State of Affairs”.